Transition Metal Complexes and Photodynamic Therapy from a Tumor-Centered Approach: Challenges, Opportunities, and Highlights from the Development of TLD1433 - Monro, Susan (Chem Rev, 2018)
Transition metal complexes are of increasing interest as photosensitizers in photodynamic therapy (PDT) and, more recently, for photochemotherapy (PCT). In recent years, Ru (II) polypyridyl complexes have emerged as the most widely studied systems for both PDT and PCT. Their rich photochemical and photophysical properties derive from a variety of excited-state electronic configurations accessible with visible and near-infrared light, and these properties can be exploited for both energy- and electron-transfer processes that can yield highly potent oxygen-dependent and/or oxygen-independent photobiological activity. Selected examples highlight the use of rational design in coordination chemistry to control the lowest-energy triplet excited state configurations for eliciting a particular type of photoreactivity for PDT and/or PCT effects. These principles are also discussed in the context of the development of TLD1433, the first Ru(II)-based photosensitizer for PDT to enter a human clinical trial. The design of TLD1433 arose from a tumor-centered approach, as part of a complete PDT package that included the light component and the protocol for treating nonmuscle invasive bladder cancer. Briefly, this review summarizes the challenges to bringing PDT into mainstream cancer therapy. It considers the chemical and photophysical solutions that transition metal complexes offer, and it puts into context the multidisciplinary effort needed to bring a new drug to clinical trial.